Las gramineas mendocinas del genero Stipa : taxonomía - Roig, Fidel A. (1964)
In order to describe phytogeographically Stipa pastures of the province of Mendoza, a previous revision of the genus is undertaken. The work begins with morphological considerations, the principal attention heing paid to the taxonomic values of the characters. A key based fundamentally an suhgenuses established by SPEcAzzINI is given, and as to Pappostipa subgenus, the author follows the judgment of Agronomic Engineer L. R. PARODI. Different taxa are described and to these the author adds the studied materíals and his observations on their distribution, systematics, etc. On the whole, 35 Mendoza species, 12 varieties and forms are named. The following new species are treated: Stirpa Semperiana, S. vatroensis. S. Ruiz Lealii, S. Parodiana, S. malalhuensis, S. barrancaensis; equally, the following varieties: S. speciosa v. parva, S. vaginata v. dilatata, S. cordobensis v. tuberculata, and the following forms: S. speciosa f. horrida, S. speciosa f. abscondita, S. vaginata f. laevis, S. vaginata f. contracta, S. vaginata f. immersa, S. vaginata f. rigida, S. chrysophylla f. minuta y S. chrysophylla f. modica. The possibility of hybrids S. speciosa - S. vaginata is discussed, going over to the synonymy of S. perrigida SPEc. The species and varieties are illustrated with analytic drawings and photographies of the types.